Altered Resting State Cortico-Striatal Connectivity in Mild to Moderate Stage Parkinson's Disease - Kwak, Youngbin; Peltier, Scott; Bohnen, Nicolaas; Müller, Martijn; Dayalu, Praveen; Seidler, Rachael D. (Frontiers in Systems Neuroscience, 2010)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder that is characterized by dopamine depletion in the striatum. One consistent pathophysiological hallmark of PD is an increase in spontaneous oscillatory activity in the basal ganglia thalamocortical networks. We evaluated these effects using resting state functional connectivity MRI (fcMRI) in mild to moderate stage Parkinson’s patients on and off L-DOPA and age-matched controls using six different striatal seed regions. We observed an overall increase in the strength of cortico-striatal functional connectivity in PD patients off L-DOPA compared to controls. This enhanced connectivity was down-regulated by L-DOPA as shown by an overall decrease in connectivity strength, particularly within motor cortical regions. We also performed a frequency content analysis of the BOLD signal time course extracted from the six striatal seed regions. PD off L-DOPA exhibited increased power in the frequency band 0.02 – 0.05 Hz compared to controls and to PD on L-DOPA. The L-DOPA associated decrease in the power of this frequency range modulated the L-DOPA associated decrease in connectivity strength between striatal seeds and the thalamus. In addition, the L-DOPA associated decrease in power in this frequency band also correlated with the L-DOPA associated improvement in cognitive performance. Our results demonstrate that PD and L-DOPA modulate striatal resting state BOLD signal oscillations and corticostriatal network coherence.